Eko-Sufisme Islam Aboge Masjid Saka Tunggal Cikakak Banyumas - Mochammad Lathif Amin (Jurnal Penelitian, 2017)
This study aims to explore the concept of environment-based spiritual ethics (eco-sufism) by exploring the values of Islamic Aboge Cikakak culture in order to answer the environmental crisis. The consciousness of the deity is transformed into a consciousness of the environment. Religion is not merely a ritual of worship, but is also practiced in solemn regard to the environment. This study used a qualitative approach with observation data collection techniques, interviews, and documentation. Data collected is related to 1) teaching, 2) ritual/tradition, 3) meaning and cultural value, 4) implementation of environmental awareness. Data analysis with fixed comparison includes data identification, categorization, and linking between categories. The result of the research shows that the root of Aboge Islamic culture is the Islamic teachings of Kejawen (Javanism) brought by Kiai Mustoleh through the Aboge calendar (Alip Rebo Wage) which is a relic of Mataram, Jaro Jab tradition, Muludan and the existence of Saka Tunggal Mosque (oldest mosque in Indonesia). The Aboge Cikakak style of Islamic ecosystem is summarized in the process of understanding the dynamic life towards God, the symbolic meaning of the names of years of the Aboge calendar (ada-ada tumandang gawe lelakon urip bola bali marang suwung), the appreciation of the unity of God-man-nature, the transformation of the servant of God (abdullah) to become khalÄ«fatullÄh or the representation of God, natas (consciousness, self-emptying), nitis (filling the nature of God into the self), and netes (overwhelming the goodness to others).